An improvement and optimization study of biodiesel production from linseed via in-situ transesterification using a co-solvent. (April 2018) - Taherkhani, M.; Sadrameli, S.M.
Abstract: The objective of this study was to investigate in-situ transesterification study of linseed with methanol in the presence of potassium hydroxide (KOH) for the production of biodiesel. The influence of tetrahydrofuran (THF) as a co-solvent was also investigated. The effect of solvent to solid ratio or solvent and co-solvent to solid ratio (SSR) (1–15 (v/w)), co-solvent to solvent (C-S/S) ratio (0.25–2.25 (v/v)), catalyst concentration (1–13 wt% oil content (w/w)), agitation rate (600–900 rpm), reaction temperature (40–60 °C) and reaction time (90–150 min) was examined to obtain the optimum biodiesel yield and biodiesel quality. The SSR, C-S/S ratio and catalyst concentration were investigated by a set of experiments that designed by "Design Expert" software in responsive surface central composite design (CCD) method with duplication of each test to improve confidence limits. The maximum methyl ester content with using the THF as a co-solvent was 93.15% when: 6.8 wt% as catalyst KOH, 10 as solvent and co-solvent to solid ratio, 0.3 as C-S/S ratio, 40  ° C as the reaction temperature, 90 min as the reaction time and 700 rpm as the agitation rate were used. Highlights: Biodiesel has been produced by in situ transesterification of linseed. A co-solvent has been used to decrease the temperature and enhance the yield. Tetrahydrofuran has been used as a co-solvent. The maximum yield of biodiesel has been obtained to be 93.15%. The optimum conditions are 6.8 wt% of catalyst, 40  ° C temperature and C-S/S of 0.3.